EFEK SELENIUM OKSIKLORIDA TERHADAP AKTIVITAS IMUNOMODULATOR DARI EKSOPOLISAKARIDA Lactobacillus plantarum - Fifi Afiati; D. C. Agustina; S. Wiryowidagdo; Kusmiati Kusmiati; Atit Kanti (Research Center for Biology-Indonesian Institute of Sciences, 2020)
Lactobacillus plantarum (LAB) is a group of lactic acid bacteria that can produce exopolysaccharide (EPS). The objective of this study was to determine the effect of adding selenium chloride oxide (SeOCl2) to the increased immunomodulatory potential of EPS L. plantarum Y-1.2. The experiment was conducted in vivo using macrophage cells of peritoneal fluid of mice induced by Staphylococcus aureus. EPS was obtained by precipitation at 4 °C. Identification test using HPLC showed that crude EPS of L. plantarum Y-1.2 containing glucose monomers for value retention times 4.198 and 4.204, crude EPS approaches the retention time of glucose BP 4.234. Testing of immuno-modulatory divided into six treatment groups. Group 1-3 as the control group, a positive control (Stimuno), negative control (crude EPS 50 mg/kg BW in mice), normal control (distilled water). Group 4-6 as the test group was given crude EPS 50 mg/kg BW in mice and selenium oxide chloride doses of 0.13 µg; 0.26 µg; 0.52 µg. The test results showed a dosage of 0.52 µg selenium chloride oxide to crude EPS of 50 mg/kg BW in mice could increase the activity and phagocytic capacity amounted to 28.06% and 28.39%